1995
DOI: 10.1039/c39950001623
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic studies of the DSP toxin DTX-4 and an okadaic acid diol ester

Abstract: Stable isotope incorporation experiments with I3C-and 180-labelled precursors show that all the carbon atoms in DTX-4 2 and an okadaic acid diol ester 3 are derived from acetate and glycolate, and also identify the acetate and glycolate derived oxygen atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 10 publications
5
87
0
Order By: Relevance
“…5) (Macpherson et al, 2003). Incorporation patterns of the OA portion of these two analogs were revealed to be identical to DTX-4 (Needham et al, 1995;Wright et al, 1996). DTX-5a and -5b have very similar side chains, the only difference being the number of carbons in the diol portion of the ester side chain.…”
Section: Dinophysis Toxinsmentioning
confidence: 79%
See 2 more Smart Citations
“…5) (Macpherson et al, 2003). Incorporation patterns of the OA portion of these two analogs were revealed to be identical to DTX-4 (Needham et al, 1995;Wright et al, 1996). DTX-5a and -5b have very similar side chains, the only difference being the number of carbons in the diol portion of the ester side chain.…”
Section: Dinophysis Toxinsmentioning
confidence: 79%
“…Carbons 1 and 2 remained unlabeled by either [1-13 C], [2-13 C]. This and the presence of vicinal hydroxyls at C1 and C2 suggest that the starter unit for this polyketide may be glycolic acid, which is also the starter unit for OA and the ester portion of DTX-4 (Needham et al, 1994(Needham et al, , 1995. Although amphidinols 2 and 4 share an identical carbon backbone, their acetate incorporation patterns were not the same.…”
Section: B Amphidinolsmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, most of the intracellular toxin in P. lima is in the form of the hydrophilic molecule DTX-4, which the results of metabolic labeling studies have suggested to be a biosynthetic precursor of OA (Needham et al, 1995; (Fig. 1).…”
Section: Okadaic Acidmentioning
confidence: 99%
“…12 These sulfated esters are essentially inactive toward PP1 and PP2A in vitro, and it has been proposed that the sulfated diesters are the initial biosynthetic products of the dinoflagellate. 13 The unique chemical structure and bioactivity of the DSP toxins have prompted extensive biosynthetic studies that have revealed much complexity. Initially it was observed that the toxins and two okadaic acid diol esters are labeled extensively from acetate in an unexpected pattern and some positions did not appear to be labeled.…”
Section: Introductionmentioning
confidence: 99%